2009
DOI: 10.1158/1055-9965.epi-09-0763
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cigarette Smoking and Human Papilloma Virus Types 16 and 18 DNA Load

Abstract: Background: Although cigarette smoking has been associated with increased human papilloma virus (HPV) detection, its impact on HPV DNA load is unknown. Methods: The study subjects were women who were positive for HPV16 and/or HPV18 at enrollment into the Atypical Squamous Cells of Undetermined Significance-Low-grade Squamous Intraepithelial Lesion Triage Study. Assessments of exposure to smoke and sexual behavior were based on self-report. Viral genome copies per nanogram of cellular DNA were measured by multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
83
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 49 publications
9
83
5
Order By: Relevance
“…Both scenarios, either alone or in combination, may determine host tissue carcinogenesis as well as viral persistence. In support of our studies, we have recently reported that a high HPV16 and HPV18 DNA load in patient cervical samples was positively correlated with cigarette smoking, suggesting that exposure to these carcinogens promotes conditions which could increase viral persistence (83).…”
supporting
confidence: 89%
“…Both scenarios, either alone or in combination, may determine host tissue carcinogenesis as well as viral persistence. In support of our studies, we have recently reported that a high HPV16 and HPV18 DNA load in patient cervical samples was positively correlated with cigarette smoking, suggesting that exposure to these carcinogens promotes conditions which could increase viral persistence (83).…”
supporting
confidence: 89%
“…There is some controversy over the impact of smoking and alcohol consumption on HPV infection in HNSCC [32][33][34][35][36].This is contrary to cervical cancer in women where smoking has an obvious synergistical effect with HPV. Some studies have suggested additive effects of smoking on HPV positive oral cavity and oropharyngeal SCC.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were incubated at 37°C for 3 h and then VOL. 85,2011 BaP INCREASES HPV31b TITER THROUGH Erk1/2 SIGNALING 4983 suspended in 1.6% methylcellulose with 1.0 M BaP or an equivalent concentration of DMSO as a vehicle control. The methylcellulose suspensions were incubated at 37°C for 48 h and then harvested for luciferase assays.…”
Section: Methodsmentioning
confidence: 99%
“…The progression to cervical cancer is associated with the integration of high-risk HPV genomes into host chromosomes (18,30). However, only a small percentage of women infected with high-risk HPV types (such as HPV16, HPV18, and HPV31) actually progress to cervical cancer (7, 21), suggesting a role for cofactors in the progression to cervical cancer.Ample epidemiological evidence exists to implicate cigarette smoking as a cofactor with HPV infection in cervical cancer progression (4,24,43,55,70,82,85). Polycyclic aromatic hydrocarbons (PAHs) are among the numerous carcinogens associated with cigarette smoking.…”
mentioning
confidence: 99%
See 1 more Smart Citation